Anthropologists Meet the 15M: The Rise of Engaged Ethnography - Roca, Beltran; Diaz-Parra, Iban; Gómez-Bernal, Vanessa (Anthropologica, 2020)
In 2011 we were involved as activists in labour, 15M, and the housing and feminist movements. Part of our scientific production became intertwined with our militancy. In addition, drawing on our research and militant experiences in the cycle of struggle that started in 2011, we noticed that the process of questioning and delegitimisation was also affecting the ambit of the social sciences. Thus, we undertook a review of the scientific literature on the 15M in order to ascertain whether the epistemological perspectives and the methodological choices of these studies were related in some way to the crisis of representation that was affecting other social institutions. This is the objective of this article. First, it explains the strategy we followed in searching the literature on the 15M. Second, it introduces the findings of the literature review on this social movement, both in Spanish and in international academic journals. Third, it proposes a typology of engaged ethnographic research. Fourth, it provides a series of limitations and precautions that researchers should bear in mind when putting this research technique into practice. Fifth, it includes a final section synthesising the main conclusions of this article regarding the anthropological production of the 15M, the types of engaged ethnography, and the limitations of this technique.